Ab initio strain engineering of graphene: opening bandgaps up to 1 eV. Issue 54 (13th June 2015) - Kerszberg, Nicolas; Suryanarayana, Phanish
<x xml:space="preserve">Abstract</x> We employ electronic structure calculations based on Density Functional Theory (DFT) to strain engineer graphene's bandgap.